2017
DOI: 10.1111/iju.13318
|View full text |Cite
|
Sign up to set email alerts
|

Difference in toxicity reporting between patients and clinicians during systemic chemotherapy in patients with urothelial carcinoma

Abstract: Toxicity underreporting by clinicians is frequent in urothelial carcinoma patients receiving systemic chemotherapy. Pretreatment quality-of-life evaluation is essential not only for quality-of-life evaluation, but also to identify potential individuals at risk for toxicity underreporting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Measurement methods were the same in serum creatinine, Alb, and uric acid between the training and validation tests. Renal function was evaluated using the eGFR at the time of diagnosis with a modified version of the abbreviated formula from the Modification of Diet in Renal Disease Study for Japanese patients . Diabetes patients were defined as those with a history of type 2 diabetes or those who met the relevant diagnostic criteria and requirements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement methods were the same in serum creatinine, Alb, and uric acid between the training and validation tests. Renal function was evaluated using the eGFR at the time of diagnosis with a modified version of the abbreviated formula from the Modification of Diet in Renal Disease Study for Japanese patients . Diabetes patients were defined as those with a history of type 2 diabetes or those who met the relevant diagnostic criteria and requirements.…”
Section: Methodsmentioning
confidence: 99%
“…Renal function was evaluated using the eGFR at the time of diagnosis with a modified version of the abbreviated formula from the Modification of Diet in Renal Disease Study for Japanese patients. [17][18][19] Diabetes patients were defined as those with a history of type 2 diabetes or those who met the relevant diagnostic criteria and requirements. Hypertension was defined as two consecutive blood pressure readings >140/90 mmHg (when not painful) or the use of antihypertensive medications.…”
Section: Evaluation Variablesmentioning
confidence: 99%
“…Fukushi et al . should be commended for their attempts to uncover the reasons why symptomatic toxicities during systemic chemotherapy are underreported by clinicians . To my knowledge, this is the first report of such theme in the field of urothelial carcinoma, and the authors hint at the importance of patient‐reported outcomes in the treatment process.…”
mentioning
confidence: 87%
“…The agenda focused on evaluating what outcomes to measure and how to measure them. Key takeaways included the following: (1) Participating stakeholders recognize the potential utility of PROs in clinical trials; (2) PRO experts within industry seek clear guidance from regulators to make the case with company leadership that PROs be gathered; (3) Continued efforts are needed to coordinate and harmonize expectations and requirements among global regulators; (4) There is a need to develop a core set of concepts as a standard expectation for trials investigating the safety and efficacy of cancer therapies; (5) A core set of concepts was proposed for lung cancer, including symptomatic adverse events (AEs), overall effect bother/impact, physical function, and disease symptoms; (6) PRO measures need to capture concepts that address patient needs, but also reflect the needs of clinicians, sponsors, regulators and health technology assessment officials; and (7) Further discussion is needed on how to communicate PRO data from trials to patients and clinicians. 1 The second meeting, the subject of the remainder of this commentary, was a follow-up roundtable discussion involving 17 lung cancer patients and leaders from the FDA.…”
mentioning
confidence: 99%
“…These studies found that patients reported higher frequency and severity of AEs compared to the clinician-recorded safety data. 4,5 Both studies were specifically designed to assess the comparability of patient and clinician reporting and did not address the comparability of reports of AEs between clinicians and patients in commercial clinical trials. Patients at our roundtable who were speaking of their experience on commercial clinical trials noted that the most common reason for under-reporting was fear of being dose-reduced or discontinued from their cancer therapy.…”
mentioning
confidence: 99%